Multi-Stakeholder Partnerships in the Development of Cultural Heritage Tourism in Binjai City - Yuni Ramadhani; Cut Nuraini; Abdi Sugiarto (International Journal of Mechanical, Electrical and Civil Engineering, 2025)
The cultural heritage buildings in Binjai City hold significant potential for cultural tourism, which can enhance the local economy and requires institutional support for development. Efforts to preserve cultural heritage while simultaneously improving the economic welfare of the community through tourism can be achieved through partnerships among involved stakeholders. Using a qualitative approach, this study analyzes the dynamics of partnerships between government, community members, business actors, academics, and the media in preserving and promoting the city’s cultural heritage. The findings indicate that multi-stakeholder partnerships are crucial for the successful development of cultural heritage tourism. Strong collaboration among various parties makes Binjai City's heritage sites attractive and sustainable tourism destinations. This research highlights the importance of cross-sector partnerships in cultural-based tourism development and provides policy recommendations for future development.